The definition of the state value in terms of functional quintessence (Law and Safety, 2024)
The article examines the issue of the quintessence of the State's axiology in terms of functional definition. For the purpose of the study, the scientific issue is divided into components which are the substantive elements of the scientific problem. First of all, the issue of the essence of the State as a legal phenomenon is revealed, which is the main basis for the emergence of the scientific problem. The relevant views of scholars on the definition of the State are also considered. It has been concluded that the State is a sovereign, political and territorial organisation of society, on the territory of which there are authorities, legal system and taxation system, as well as other additional elements. The author further provides the features inherent in the State which constitute its ontology.Based on a comprehensive analysis of the essence of the concept of “state”, the article presents some theories of the origin of the state which reflect the purpose of its emergence and existence. The most common theories of the origin of the State include: patriarchal, contractual, violence, organic, and psychological. After analysing some of the theories, the author concludes that the purpose of the State’s emergence and existence is to unite society, resolve disputes and develop it.The quintessence and diversity of the functions of the State are analysed. As a result, it has been concluded that the functions of the State are a set of activities and processes whose impact is directed at society. Differentiation of functions also has different manifestations. Some scholars distinguish between basic and additional functions, some – internal and external. Internal functions include, for example, regulatory, defence, etc., while external functions include diplomatic and economic (in the context of foreign activities). Based on the analysis of the functions of the State which reflect the directions of its influence on society and which are regulatory in nature (and the very essence of the State is organisational in nature), the article concludes that the axiology of the State in terms of the functional definition is to organise society with the help of its inherent properties and to regulate social relations on the basis of its existing functions with a view to social development.
Keywords: state; value; functions; society; regulation.